The kynurenine pathway in traumatic brain injuries and concussion - Dehhaghi, Mona; Heng, Benjamin; Guillemin, Gilles J. (Frontiers in Neurology, 2023)
Up to 10 million people per annum experience traumatic brain injury (TBI), 80–90% of which are categorized as mild. A hit to the brain can cause TBI, which can lead to secondary brain injuries within minutes to weeks after the initial injury through unknown mechanisms. However, it is assumed that neurochemical changes due to inflammation, excitotoxicity, reactive oxygen species, etc., that are triggered by TBI are associated with the emergence of secondary brain injuries. The kynurenine pathway (KP) is an important pathway that gets significantly overactivated during inflammation. Some KP metabolites such as QUIN have neurotoxic effects suggesting a possible mechanism through which TBI can cause secondary brain injury. That said, this review scrutinizes the potential association between KP and TBI. A more detailed understanding of the changes in KP metabolites during TBI is essential to prevent the onset or at least attenuate the severity of secondary brain injuries. Moreover, this information is crucial for the development of biomarker/s to probe the severity of TBI and predict the risk of secondary brain injuries. Overall, this review tries to fill the knowledge gap about the role of the KP in TBI and highlights the areas that need to be studied.